BIAYA KARBON, BIAYA LIMBAH DAN DAMPAKNYA PADA BIAYA MODAL: KASUS DI INDONESIA - Angraini, Kiki; Indayani, Indayani; Mulyany, Ratna (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2025)
Green economy policy No. 21 of 2022 concerning the Implementation of Carbon Economic Values has become a necessity in Indonesia. Environmental damage arising from greenhouse gas emissions requires companies to take responsibility and establish strategies to combat and mitigate negative impacts. Carbon costs and waste costs are corporate policy instruments that can encourage greenhouse gas emission reductions. This study investigates the effect of carbon costs and waste costs on the cost of capital in companies listed on the Indonesia Stock Exchange. The population in this study consisted of 912 manufacturing companies listed on the Indonesia Stock Exchange from 2021 to 2023. Secondary data sources were from company sustainability reports. The sample selection technique used purposive sampling. The research sample consisted of 85 companies with a total of 255 observations over 3 years. This study used Structural Equation Model-Partial Least Square (SEM-PLS) version 4.0 analysis. The results indicate that waste costs affect the cost of capital, while carbon costs do not. While carbon costs can influence a company's strategic decisions, their impact on the cost of capital is not always significant, especially in sectors not subject to strict emissions regulations. While waste costs indicate that poor waste management can potentially increase capital costs, good management can reduce these costs by reducing corporate risk.